Unjuk Kerja Alat Pemotong Pelepah Sawit Tipe Egrek Secara Manual dan Mekanis Menggunakan Mesin Husqvarna 327 LDx - Forky Indra Kano; Sandi Asmara; M. Zen Kadir; Siti Suharyatun (abe.fp.unila.ac.id, 2023)
The cutting of palm frond using sickle manually produces low productivity and high accident risk. Therefore, it is required a mechanical sickle that can increase its productivity and reduces the risk of a work accident. The purpose of this research was to determine work capacity, workload, and energy requirement. The treatment in this research was based on the differences of high oil palm trees (5 m and 7 m) and the number cut off fronds (5, 10 and 15). The result showed the comparison of the highest capacity between manual and mechanical sickle at 5 m height counted 494 and 743 fronds/hour and at 7 m height of 676 and 817fronds/hour. In workload testing there is data that is needed to rest on the operator, that is on testing data of 10 fronds and data of 15 fronds manually with tree height of 5 m and 7 m and on other test data including activities that do not cause operator fatigue. The range energy requirement for oil palm frond cutting process of 5 fronds, on the height of trees 5 m and 7 m all data are included in the classification of light workloads with Energy Expenditures with a range of 2.5-5.0 Kcal/minute. The range energy requirement for oil palm frond cutting process of 10 fronds and 15 fronds, on the height of trees 5 m and 7 m all data are included in the classification of moderate workloads with Energy Expenditures with range 5,0-7,5 Kcal/minute. Keyword: A Mechanical Sickle Type with Husqvarna Machine 327 LDx, Oil Palm Frond, Manual Sickle Type.